POLA DISTRIBUSI PARASIT PADA IKAN BELANAK (Mugil cephalus) YANG TERTANGKAP DI PERAIRAN SEKITAR CILACAP - Sofiyatun, Eny (Sainteks, 2012)
And Segara Anakan Turtle Bay (river Donan) is biodiversity-rich aquatic environments. Fisheries resources is one that has many potential diamanfaatkan, both for local and international needs. The fish is never separated from the life of a parasite that is also a component in an ecosystem. This study aims to determine the distribution pattern of parasites, both ectoparasites and endoparasites, the mullet fish (M. Cephalus) who was caught in the waters around Cilacap, covering waters Segara Anakan and Turtle Bay. The method used in this research is survey method with fish sampling is purposive sampling of fish mullet (M. Cephalus) of the families Mugilidae from two locations, namely the Turtle Bay and Segara Anakan (river Donan). The study was conducted in May and July 2008. The number of samples of fish taken was 30 individuals for each location. Parasite species found in M. Cephalus of Turtle Bay is more diverse than Segara Anakan (river Donan). Based on the analysis of the value of x (mean intensity) and S2 (standard deviation) is known that the distribution pattern of Caligus sp. found in M. Cephalus of the two sites showed a similar pattern, which is clustered. More clumped distribution pattern shown in Nothobomolochus sp. and Digenea indetermination. A uniform distribution pattern shown in Ergasillus sp. and Metamicrocotyla sp., whereas a random distribution pattern found in the Monogenea indetermination, Cymothoa sp., and Acanthocephala. Differences in the distribution pattern of each parasite species were found showing the survival of free-living stages and the ability to infect the host. In addition, also influenced by host specifity factor (predilection), as well as competition and predation.Keywords: distribution pattern, Mugil Cephalus, Segara Anakan, Turtle Bay.